Characterization of Mixed Biomass Pellet Made from Oil Palm and Para-rubber Tree Residues - Wassachol Wattana; Siwimon Phetklung; Watcharakit Jakaew; Songamorn Chumuthai; Phurinut Sriam; Nantita Chanurai (My University, 2017)
In this study, the potential of the important economic crops of Southern Thailand for pellet making was utilized. The biomass pellets were prepared from oil palm leaves (PL) and frond (PF), para-rubber leaves litter (PAL) and branch (PB) and their blend (mixing of 50 wt.% of two materials). The raw materials which collected from local plantation were cleaned, dried and milled into small particles less than 1 mm and then continued with pellet forming by a single unit press in a laboratory under the temperature and pressure of 130°C and 350 psi. Some characteristics were analyzed to evaluate quality of pellet, i.e. moisture content, density, ash content, calorific value. Moreover, the combustion behavior was investigated by means of thermogravimetry analysis. The lowest ash content of 2.27% and 2.82% were received from PB in case of pure pellet and PB+PAL in case of mixed pellets, respectively. The calorific values of pure pellets were 16.05, 17.68, 18.71 and 19.64 MJ/kg for PF, PL, PB and PAL, respectively. The combustion characteristics were exhibited in the ignition and burnout temperature, which drawn from TG curved. The burnout temperature was improved with higher in all cases of mixed biomass pellet. The characteristics of mixed biomass pellets differed from pure biomass pellets which contribute to the further improve its quality.
Keywords: Pellet; Heat of combustion; Pelletizing; Thermochemical Biomass Conversion Processes